Being cruel to be kind - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Patrick Mphaka reporting on the work of FINCA who, despite having a strict programme of repayments, have given small business loans to over 20,000 Malawians.